PENGARUH BODY MASSAGE IBU POST PARTUM TERHADAP PENINGKATAN PRODUKSI ASI - Saraha, Rosida Hi; Suaib, Nurkila (Poltekkes Kemenkes Bandung, 2024)
A decrease in breast milk production in the first few days after birth can be caused by a lack of stimulation of the hormones prolactin and oxytocin. This study aimed to determine the effect of postpartum maternal body massage on breast milk production. This research was located in the Working Area of Bahari Berkesan Health Center, in January-November 2022. The sample in this study was 20 post breastfeeding postpartum mothers. The sampling technique used was purposive sampling technique. The research design used was quasi-experimental with a One Group Pre and Post-Test Design. Researchers performed body massage on a group of breastfeeding postpartum mothers by taking 3 measurements of the baby's weight and 2 body massages. Based on the test results using the Spearman Rank Correlation, a significance value of 0.060 > 0.05, indicating that there was no influence on the first weight gain. Meanwhile, the test results between body massage and the baby's weight gain in the second measurement were 0.018, and the third weight measurement was 0.044, because the significance value was <0.05, which means that there was an influence between massage and the baby's weight gain in the second and third measurements. The study concluded that body massage can increase breast milk production by measuring the baby's weight. It is recommended Further research is needed to explore the specific mechanisms through which body massage influences breast milk production.